2021
DOI: 10.21037/atm-20-2003
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of second primary malignancies after cervical cancer using a competing risk model: implications for prevention and surveillance

Abstract: Background: Previous studies have reported an increased risk for second primary malignancies (SPMs) after cervical cancer (CC). This study aims to quantify and assess the risk of developing SPMs in long-term survivors of CC.Methods: A population-based cohort of CC patients aged 20-79 years was obtained from the Surveillance, Epidemiology, and End Results (SEER) database. A competing risk model and corresponding nomogram were constructed to predict the 3-, 5-, and 10-year cumulative risks of SPMs. A Fine-Gray p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“… 36 Patients with cervical cancer with SPM have been found to experience better OS within 6 years than those without SPM. 38 However, this result may be inconsistent with clinical observations. The first possible reason for this discrepancy is that HPC might have a shorter survival time than other types of SPM tumors; the second is that the follow-up time might not have been long enough.…”
Section: Discussionmentioning
confidence: 81%
“… 36 Patients with cervical cancer with SPM have been found to experience better OS within 6 years than those without SPM. 38 However, this result may be inconsistent with clinical observations. The first possible reason for this discrepancy is that HPC might have a shorter survival time than other types of SPM tumors; the second is that the follow-up time might not have been long enough.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, in competing risk events, the Fine and Gray proportional sub-distributed hazard method is advocated ( 56 , 57 ). To the best of our knowledge, researchers have used the Fine and Gray proportional subdistributed hazard method to construct competing risk models for multiple primary cancers associated with cervical cancer ( 58 ) and colorectal cancer ( 59 ). However, competing risk models for spPDAC cancer-specific mortality have not yet emerged.…”
Section: Discussionmentioning
confidence: 99%
“…So far, there has been no consensus on the role of black ethnicity in poorer survival of cervical cancer, 24 , 25 , 26 , 27 , 28 , 29 even after controlling for treatment patterns. 30 , 31 In this study, we selected patients who underwent at least one type of radiation therapy or surgery, but we still found that being black was associated with poorer overall survival, and being Asian was a protective factor.…”
Section: Discussionmentioning
confidence: 99%